(untitled) (Global Journal of Sciences, 2025)
This research evaluates the impact that capital reduction announcements have on the stock prices of firms that are listed on the Saudi Stock Exchange (Tadawul) between 2020 and 2024. Specifically, the study will focus on the period between 2020 and 2024. This research makes use of the event study methodology in order to assess the effectiveness of the market as well as the actions of investors in response to business events. In order to achieve this task, it is necessary to evaluate the course of market responses and the timing of those reactions. To be more specific, the objective of this study is to analyze whether or not the reduction in capital serves as an early warning sign of financial difficulties, or whether or not it is a deliberate process of financial restructuring with the idea of boosting the organization’s worth over the long run. According to the findings of empirical research, announcements of a decrease in capital at the time of the event do not evoke a market reaction that is statistically significant in a negative direction. After an initial period of investor concern, the data suggests that there was a relatively favorable cumulative impact. This is in contrast to the previous statement. The fact that this is the case shows that market participants may see these declarations as components rather than indicators of a crisis or of aggressive financial management. The purpose of this study is to contribute to the knowledge of financial restructuring, company signaling, and market efficiency in emerging countries. The dissemination of data extracted from the expanding Saudi capital market is how this objective is fulfilled. These results shed light on the need of conducting an evaluation of activities that are targeted at decreasing capital within the context of a strategic governance framework that is in accordance with the goals of Saudi Arabia’s Vision 2030. As a result of this, they bring attention to the possible importance that these activities may have in increasing the confidence of investors and assuring the organization’s capacity to continue operating financially in the future.